Framework for Implementing Green Supply Chain Practices in Indonesian Small and Medium Enterprises - Aini, Qurotul; Hardini, Marviola; Hikam, Ihsan Nuril; Green, Thomas (APTISI Transactions on Management (ATM), 2025)
The urgent need to address climate change, environmental degradation, and resource depletion has driven the adoption of sustainable business practices globally. For Small and Medium Enterprises (SMEs), particularly in developing countries such as Indonesia, transitioning toward sustainability presents both challenges and opportunities. Green Supply Chain Management (GSCM) offers a comprehensive approach to integrating environmental considerations into every stage of the supply chain, from sourcing raw materials to end-of-life product management. This study develops a practical GSCM framework tailored for Indonesian SMEs, using a qualitative multiple-case study method across three sectors: food, handicrafts, and logistics. Data collection methods included semi-structured interviews, on-site observations, and document analysis, followed by thematic coding and cross-case synthesis. The resulting framework identifies five interrelated components: supplier collaboration, eco-friendly material selection, waste reduction strategies, energy efficiency optimization, and sustainability performance monitoring. The framework is validated through triangulation of data sources and feedback from SME stakeholders. By aligning with the United Nations Sustainable Development Goals (SDGs), particularly Goals 12 and 13, this study provides actionable insights for policymakers, SME owners, and practitioners seeking to enhance sustainability while maintaining operational efficiency.